Forearm fractures - are we counting them all? An attempt to identify and include the missing fractures treated in primary care - Cecilie Dahl; Eyvind Ohm; Siri Marie Solbakken; Nudrat Anwar; Kristin Holvik; Christian Madsen; Frede Frihagen; Åshild Bjørnerem; Frida Igland Nissen; Lene B. Solberg; Tone Kristin Omsland (Taylor & Francis Group, 2023)
AbstractObjective Norway has a high incidence of forearm fractures, however, the incidence rates based on secondary care registers can be underestimated, as some fractures are treated exclusively in primary care. We estimated the proportion of forearm fracture diagnoses registered exclusively in primary care and assessed the agreement between diagnosis for forearm fractures in primary and secondary care.Design Quality assurance study combining nationwide data from 2008 to 2019 on forearm fractures registered in primary care (Norwegian Control and Payment of Health Reimbursement) and secondary care (the Norwegian Patient Registry).Setting and patients Forearm fracture diagnoses in patients aged ≥20 treated in primary care (n = 83,357) were combined with injury diagnoses for in- and outpatients in secondary care (n = 3,294,336).Main outcome measures Proportion of forearm fractures registered exclusively in primary care, and corresponding injury diagnoses for those registered in both primary and secondary care.Results Of 189,105 forearm fracture registrations in primary and secondary care, 13,948 (7.4%) were registered exclusively in primary care. The proportion ranged from 4.9% to 13.5% on average between counties, but was higher in some municipalities (>30%). Of 66,747 primary care forearm fractures registered with a diagnosis in secondary care, 62% were incident forearm fractures, 28% follow-up controls, and 10% other fractures or non-fracture injuries.Conclusion An overall small proportion of forearm fractures were registered only in primary care, but it was larger in some areas of Norway. Failing to include fractures exclusively treated in primary care could underestimate the incidence rates in these areas.